EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS), NUMBERED HEADS TOGETHER (NHT), DAN THINK PAIR SHARE (TPS) PADA MATERI LINGKARAN DITINJAU DARI KREATIVITAS BELAJAR MATEMATIKA SISWA SMP NEGERI DI KABUPATEN SUKOHARJO - Ratih Kusumaningrum; Budiyono Budiyono; Sri Subanti (Jurnal Pembelajaran Matematika, 2015)
Abstract: The objective of research was to find out the effect of Two Stay To Stray (TSTS), Numbered Heads Together (NHT), and Think Pair Share (TPS) types of cooperative learning model on the student learning achievement viewed from mathematics learning creativity. This study was a quasi experimental research with a 3 x 3 factorial design. The population of research was all of the 8th graders of Junior High Schools in Sukoharjo Regency. The sample was taken using stratified cluster random sampling. The instruments used for collecting data were mathematics learning achievement test and mathematics learning creativity questionnaire. Considering the hypothesis testing, the following conclusions could be drawn. 1) TSTS learning model provide better learning achievement then NHT and TPS learning model did, and NHT and TPS learning model provided equally good learning achievement. 2) The students with high mathematics learning creativity had mathematics learning achievement better than those with medium and low learning creativity did, and those with medium and low learning creativities had equally good learning achievement. 3) In high and low mathematics learning creativity levels, the students treated with TSTS, NHT, and TPS learning model had equally good mathematics learning achievement. At medium mathematics learning creativity level, the students treated with TSTS  and NHT learning models had equally good mathematics learning achievement, those treated with NHT and TPS learning models had equally good mathematics learning achievement, those treated with TSTS learning model had better mathematics learning achievement than those treated with TPS learning model. 4) In TSTS learning model, the students with high and medium learning creativity had equally good mathematics learning, those with medium and low learning creativity had equally good mathematics learning, those with high learning creativity had learning achievement better than the students with low mathematics learning creativity. In NHT and TPS learning model, the students with high, medium, and low mathematics learning creativity had better mathematics learning achievement.Keywords: Two Stay Two Stray (TSTS), Numbered Heads Together (NHT), Think Pair Share (TPS), Mathematics Learning Creativity.